Agglomeration and Economic Development: Import Substitution Vs. Trade Liberalization. - Puga, D; Venables, A (CEPR, 1998)
This paper analyses a model of economic development in which international inequalities in the location of industry and income are supported by the agglomeration of industry in a subset of countries. Economic development may not be a gradual process of convergence by all countries, but instead involves countries moving sequentially from the group of poor countries to the group of rich countries. The role of trade policy in promoting industrialization is studied. While both import substitution and unilateral trade liberalization may be 'successful' in attracting industry, they attract different sectors and welfare levels are higher under trade liberalization.